Circulating cultures : exchanges of Australian Indigenous music, dance and media - Harris, Amanda, 1976- (ANU Press, 2014)
Circulating Cultures is an edited book about the transformation of cultural materials through the Australian landscape. The book explores cultural circulation, exchange and transit, through events such as the geographical movement of song series across the Kimberley and Arnhem Land; the transformation of Australian Aboriginal dance in the hands of an American choreographer; and the Indigenisation of symbolic meanings in heavy metal music.